HOME VERSUS OFFICE BIOFEEDBACK THERAPY FOR DYSSYNERGIC DEFECATION: PARALLEL ARM RANDOMIZED CONTROLLED TRIAL - Rao, Satish SC (Lancet Gastroenterol Hepatol, 2018)
BACKGROUND: Office-based biofeedback therapy (OB) is efficacious for constipation with dyssynergic defecation (DD). However, it requires skilled staff, multiple visits and only available in selected centers. Whether home-based biofeedback therapy (HB) is also effective is not known. METHODS: In a randomized controlled trial, patients with DD (Rome III) received either OB or HB. OB comprised of therapist-guided six biweekly sessions of pelvic floor training. HB comprised of self-training at home, 20 minutes, twice a day, after self-inserting a probe attached to a display box that provided individual, performance-specific, visual feedback. Anorectal physiology and daily symptom diary were assessed and compared. Subjects with normalization of dyssynergic defecation and ≥1 increase in number of complete spontaneous bowel movements (CSBM)/week at 3 months were considered responders. Cost outcomes were assessed using hospital billing records and questionnaires. ITT non-inferiority analyses and per protocol analyses were performed using the one-sided t-test with a margin (bound) added to the null value. Clinical trials.gov no NCT03202771. RESULTS: 100 subjects (96 F) participated, 83 completed [Home = 38/50, office= 45/50]. Thirty-four (68%) patients were responders in HB and 35/50 (70%) in OB. The number of CSBM/week, dyssynergia pattern, balloon expulsion time, digital maneuver use and bowel satisfaction improved significantly (p<0.0001) from baseline with both treatments. The effect of HB was non-inferior to OB for the primary subjective and physiologic outcomes of number of CSBM/week, bowel satisfaction, and balloon expulsion time in both ITT and per protocol analyses, and for dyssynergia in the per protocol analysis. Home device was well tolerated. There were no adverse events. HB incurred significantly lower costs than OB (p<0.01), with a saving of $860.00. CONCLUSION: HB significantly improves bowel symptoms and physiology and is as effective as OB. HB is well tolerated, less costly and should be preferred treatment for DD. FUNDING: NIH grant RO1 DK 57100–05 and grant RR00059 from the General Clinical Research Centers program, National Center for Research Resources.